ANALYSIS OF TRANSLATION TECHNIQUES USED IN “THE KISSING BOOTH” MOVIE SUBTITLE - Dwi Nopiyadi; Rahma Ayuditya Putri (Tomorrow's Education Journal, 2023)
This research aims to analyze the translation techniques of subtitling used on The Kissing Booth movie. This research uses qualitative method. The content analysis is used as a method to identify and analyze the translation techniques in The Kissing Booth movie. Every utterance in five scenes of The Kissing Booth movie are the unit of analysis of this research. The source language is English and the target language is Indonesian Language. The result proves that the translation technique that mostly appears on The Kissing Booth movie (2018) is reduction with eight data (26.67%). The second highest is discursive creation and transposition. Both of them have six data (20.00%). In the third position there is compensation with a total of five data (16,67%). Next, there are linguistic amplification and borrowing. The results show that both of them have two data (6,67%). The last one is literal translation with only one data (3,33%).